2020
DOI: 10.1021/acsomega.9b04268
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for Improving the Flow of Waxy Crude Oil Using Thermochemical Fluids: Experimental and Simulation Study

Abstract: This article focuses on the flow assurance of waxy crude oil using an environmentally benign and cost-effective approach involving thermochemical reaction. The study incorporates experimental and simulation works to evaluate heat and pressure generation potentials and heat transfer efficiency of the thermochemical fluids. Experimental results reveal that at the concentration (1 M) of thermochemical fluid (TCF) ranging between 14 and 33% v/wt of the waxy oil, sufficient heat could be generated to raise the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…First, the mechanical and rheological properties of paraffin waxes are highly relevant to flow assurance of waxy crude oils and the removal of existing wax deposits in pipelines . Recently, Alade et al have investigated the softening of wax deposits using thermochemical reactions to increase the oil temperature . It is known that the physical properties of the crystal and rotator phases differ, which has been quantified by measurements of the elastic constants and the speed of sound .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the mechanical and rheological properties of paraffin waxes are highly relevant to flow assurance of waxy crude oils and the removal of existing wax deposits in pipelines . Recently, Alade et al have investigated the softening of wax deposits using thermochemical reactions to increase the oil temperature . It is known that the physical properties of the crystal and rotator phases differ, which has been quantified by measurements of the elastic constants and the speed of sound .…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, Alade et al have investigated the softening of wax deposits using thermochemical reactions to increase the oil temperature. 77 It is known that the physical properties of the crystal and rotator phases differ, which has been quantified by measurements of the elastic constants and the speed of sound. 78 Wang et al investigated the viscoelastic properties of paraffin wax and found that the dynamic moduli were highly temperature-dependent in the crystal phase and dropped by over 1 order of magnitude upon crystal−rotator transition.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Crude oil is often characterized by the hydrocarbons in it. Paraffins account for a greater percentage of hydrocarbons in crude oil [20]. Because of the different hydrocarbon contents in them, crudes from different parts of the world often have varying colors and viscosities.…”
Section: Classification Of Crude Oilmentioning
confidence: 99%
“…Limited by the actual flow area of the wellbore, the production of the well is reduced and the pumping cost is increased. 1 5 If the deposits are not removed in time, it may even threaten the safety of transmission in serious cases. 6 9 Wax deposition has always been a hot issue in the field of petroleum exploration and the development and pipeline transportation.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of petroleum production, the pipe diameter decreases with the buildup of wax deposits. Limited by the actual flow area of the wellbore, the production of the well is reduced and the pumping cost is increased. If the deposits are not removed in time, it may even threaten the safety of transmission in serious cases. Wax deposition has always been a hot issue in the field of petroleum exploration and the development and pipeline transportation. Detailed research has been conducted on it by scholars for many years.…”
Section: Introductionmentioning
confidence: 99%